Urban Space and Contingent Meanings of the Built Environment in Nigeria (2019)
The re-interpretation of the spatial character of the city is continuously re-making the appearance of the urban centres in the contemporary milieu. This paper argues that urban transformations are born out of conflicts resulting in spatial urban boundaries becoming blurred and creations of vulnerable urban spaces. Such spaces are continuously being renegotiated through the activities and reactions in the built environment due to the actions o f different stakeholders and powerful actants. Using methodological approaches that include interviews, participant observation, and topographical analysis, it further examines the conflict or tension as change takes place during inner city development. By identifying various negotiations amongst the urban users with different interests and choices and ways they have appropriated urban space in recent times in Southwest Nigeria Findings revealed that powerful actants have problematized, mobilized and deployed resources in order to achieve their vision ofwhat form the built environment should take, and not necessarily what is sustainable. The paper concludes by underscoring the preservation of the essential parts o f the urban character and cultural life of the city